Assessing the impact of B2C e-commerce in the apparel industry: A logistics perspective - Chiara Siragusa; Arianna Seghezzi; Angela Tumino; Riccardo Mangiaracina (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: The significance and pervasiveness of B2C e-commerce raise the question about its impact on employment under a social sustainability perspective. This study is aims to quantify the labour demand in logistics comparing the e-commerce order fulfilment process and the traditional brick-and-mortar one. Methodology: An activity-based model is developed to represent a traditional retailer that both operates online and offline within the apparel industry in the Italian context. The working time related to an average single piece of apparel has been derived for each manual activity performed along the distribution chain. Findings: Results are determined by the development of representative scenarios and the main variables affecting the employment are identified. Evidence shows that e-commerce requires more labour than brick-and mortar retail either in the traditional configuration of home delivery or delivery to parcel lockers. The decisive phase is the last-mile delivery, which requires the majority of labour time, both because of driving time and the consignment itself. Originality: The main originality of the work lies in the perspective adopted to study the employment impacts of B2C e-commerce, providing an analytical contribution to the social sustainability literature of logistics.
urn:nbn:de:gbv:830-882.0162409; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; Sustainability